PELATIHAN PERANCANGAN KEMASAN UNTUK MENINGKATKAN KUALITAS PRODUK DI PABRIK KRUPUK SGM - Tri Wisudawati; Ecclisia Sulistyowati (Politeknik Negeri Sriwijaya, 2020)
Various facilities that are felt in utilizing information technology in the industry are very helpful in marketing activities ranging from marketing products, finding customers to buying and selling transactions that can increase competitiveness so that it can develop more rapidly. The development of technology in facing business competition is so rapid, especially in the field of marketing, so that the home industry business